2015
DOI: 10.1021/acs.bioconjchem.5b00107
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiscs as a Modular Platform for Multimodal MR-Optical Imaging

Abstract: Nanodiscs are monodisperse, self-assembled discoidal particles that consist of a lipid bilayer encircled by membrane scaffold proteins (MSP). Nanodiscs have been used to solubilize membrane proteins for structural and functional studies and deliver therapeutic phospholipids. Herein, we report on tetramethylrhodamine (TMR) tagged nanodiscs that solubilize lipophilic MR contrast agents for generation of multimodal nanoparticles for cellular imaging. We incorporate both multimeric and monomeric Gd(III)-based cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 36 publications
0
28
1
Order By: Relevance
“…This observation suggests that labeled Nanodiscs can be used as a probe for immunostaining organells in various cell lines, although results of this work do not distinguish between uptake of intact Nanodiscs and penetration of labeled MSP into the cell. An earlier study demonstrated that HeLa cells absorb lipids labeled with a Gd 3+ chelating complex from Nanodiscs by lipid exchange, 459 which may suggest that Nanodiscs could disassemble, at least partially, during this process. In this latter work, Nanodiscs with rhodamine tag on MSP were assembled together with a maximum content of monomeric Gd 3+ -chelating lipids corresponding to ~48 Gd 3+ (38%) per disc.…”
Section: Nanodisc Applications In Biotechnology and Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggests that labeled Nanodiscs can be used as a probe for immunostaining organells in various cell lines, although results of this work do not distinguish between uptake of intact Nanodiscs and penetration of labeled MSP into the cell. An earlier study demonstrated that HeLa cells absorb lipids labeled with a Gd 3+ chelating complex from Nanodiscs by lipid exchange, 459 which may suggest that Nanodiscs could disassemble, at least partially, during this process. In this latter work, Nanodiscs with rhodamine tag on MSP were assembled together with a maximum content of monomeric Gd 3+ -chelating lipids corresponding to ~48 Gd 3+ (38%) per disc.…”
Section: Nanodisc Applications In Biotechnology and Medicinementioning
confidence: 99%
“…These Nanodiscs proved to be very efficient contrasting agents in T 1 magnetic resonance imaging at highest tested field (7 Tesla), as they are easily absorbed with long retention times (up to 72 hours) by HeLa and MCF7 cells and allow signal accumulation for sufficiently long times. 459 Nanodiscs with trimeric Gd 3+ -chelates also were assembled with 28% loading (137 Gd 3+ per disc), but were less efficiently absorbed to cells, as judged by fluorescently labeled MSP. Interestingly, cellular proliferation experiments with cells labeled with Gd 3+ -loaded Nanodiscs show no decrease in the growth rate and high retention of Gd 3+ in the cell culture.…”
Section: Nanodisc Applications In Biotechnology and Medicinementioning
confidence: 99%
“…There are numerous reports of Gd(III)–nanoparticle formulations with high cell labeling efficiency and imaging efficacy. 1,2,5,10,2023 In particular, carbon-based nanomaterials bearing Gd(III) ions such as gadographene, gadofullerene, and gadonanotubes have been explored. 21,2427 However, a majority of these constructs have not enabled long-term cell labeling and fate mapping in vivo due to limited stability in biological media.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that this effect is unlikely to be the result of relaxivity changes upon intercalation into the cell membrane because previously lipophilic agents were shown to exhibit the same relaxivity in solution and bound to nanoparticle cell membrane mimics (called Nanodiscs). [30] Overall, these data show that while all the lipophilic complexes produce significant contrast compared to cells incubated with ProHance®, complex 3 is the most promising for high field imaging.…”
Section: Resultsmentioning
confidence: 82%